1988
DOI: 10.1139/v88-148
|View full text |Cite
|
Sign up to set email alerts
|

Infrared multiphoton absorption and decomposition of ethanol vapour

Abstract: Can. J. Chem. 66, 857 (1988). Multiphoton absorption (MPA) by ethanol has been studied using pulsed HFand C02 lasers. For the same laser fluence, a C02 laser excites the ethanol molecule to a much higher energy than an HF laser. The multiphoton decomposition (MPD) of methanol has been studied using the 9P(16) C02 laser line for pulse widths of 10 and 60 ns. The major decomposition channel produces C2H4 and HZO. However, other decomposition channels, resulting in the products CH3CH0, C2H6, CH4, and C2H2, are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…As reported earlier (12), the addition of O2 as a radical scavenger had no effect on the molecular elimination reactions [ l a ] , [ l b ] , or [ I c]; however, it completely suppressed the production of ethane. This indicated that ethane is produced following the radical reaction [Id], which produces CH3.…”
Section: Results and Discussion Ethyl Alcohol Plus Iodinesupporting
confidence: 60%
“…As reported earlier (12), the addition of O2 as a radical scavenger had no effect on the molecular elimination reactions [ l a ] , [ l b ] , or [ I c]; however, it completely suppressed the production of ethane. This indicated that ethane is produced following the radical reaction [Id], which produces CH3.…”
Section: Results and Discussion Ethyl Alcohol Plus Iodinesupporting
confidence: 60%
“…The assumed dissociation channel leading to H 2 O and C 2 H 4 has been confirmed in IR multiphoton excitation experiments of C 2 H 5 OH. 73,74 To our knowledge a deconvoluted dependence of product yields F P upon laser fluence has not yet been published. It would be possible to detect ethylene products by direct IR absorption.…”
Section: E Master Equation Calculations For the Ir Multiphoton Excitmentioning
confidence: 99%